On the question of loss characteristics estimation in queueing systems with limited customers’ total volume - Tikhonenko, Oleg; Ziółkowski, Marcin; Stachowiak, Sylwia (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
In this paper, we consider the problem of loss characteristics estimation for queueing systems with random volume customers and limited memory buffer. This issue is of key importance in the processes of analysis and design of many real IT systems with stochastic operation. Main results obtained in this work are formulae allowing to calculate exact values of loss probability and probability of losing a unit of information, or their estimations in the case of systems for which getting exact characteristics is not possible. We focus on two classes of models: first, in which customer’s service time and his volume are independent, and second, in which these random variables are dependent. Finally, we present practical results for some special cases of models belonging to these two classes illustrating them with some numerical computations.